Autonomy-Supportive Faculty, Students' Self-System Processes, Positive Academic Emotions, and Agentic Engagement: Adding Emotions to Self-System Model of Motivational Development - Bordbar, Maryam (Frontiers in Psychology, 2021)
The aim of this study was to investigate mediating roles of students' self-system processes and positive academic emotions in a relationship between supporting autonomy and agentic engagement. In This research structural equation modeling was used to analyze a conceptual model. The sample consisted of 452 undergraduate students of Ferdowsi University of Mashhad. The research instruments included the autonomy-supportive environment inventory, the self-system processes questionnaire, three questionnaires of academic emotions, and the agentic engagement scale. The findings showed that supporting autonomy had an indirect effect on students' achievement emotions, via self-system processes. Self-system processes had direct and indirect effects on agentic engagement, via positive academic emotions. Supporting autonomy had an indirect effect on agentic engagement by mediating role of self-system processes and positive academic emotions. Accordingly, emotions are proximal determinants of agentic engagement. Supporting autonomy and self-system processes affect agentic engagement from the pathway of academic emotions. Therefore, in addition to environmental factors and self-appraisals, it is necessary to consider students' emotional experiences to promote agentic engagement in learning settings.